Transpupillary thermotherapy efficiency in the combined treatment of small calcified retinoblastoma - S. V. Saakyan; R. A. Tatskov; E. B. Myakoshina; T. L. Ushakova; V. G. Polyakov (Российский офтальмологический журнал, 2018)
Purpose: to evaluate the effectiveness of transpupillary thermotherapy (TTT) of small calcified retinoblastomas (SR) having various calcification degrees. Material and methods. The results of treatment of 111 children (92 eyes, 198 tumors) with small calcified retinoblastomas by TTT were analyzed. All tumor foci were divided into 3 groups: Group 1, with tumor size of 1.0 mm or less with a low degree of calcification in the form of small specks of single grains (69 tumors); group 2, with tumor sizes between 1.1 and 2.0 mm and calcination degrees varying from small singular inclusions to a third of tumor volume (61 tumors), and group 3, with tumor sizes between 2.1 and 3.0 with calcifications claiming from one third to three fourths of tumor volume (68 tumors). Results. TTT proved effective after one application in 82.6 % of Group 1 cases, 70.5 % of Group 2 cases, and in 38.2 % of Group 3 cases. The presence of calcinates in the tumor stroma is no contraindication for TTT. Conclusion. TTT used in combined eye preserving RB treatment destroys in most cases calcified tumor foci, and allows for an extended list of indications to eye preserving treatment, which enables the preservation of the eye not only as a cosmetic but as a functional organ. For citations: Saakyan S.V., Tatskov R.A., Myakoshina E.B., et al. Transpupillary thermotherapy efficiency in the combined treatment of small calcified retinoblastoma. Russian ophthalmological journal. 2017; 10 (3): 71-77. doi: 10.21516/2072-0076-2017-10-3-71-77 (in Russian).